An Analysis Of Illocutionary Acts Performed By Gala In Tuo Nifaro, A Movie by Brams Zega - Pangaribuan, Rotua (The Explora, 2020)
This research deals with the types of Illocutionary Acts in Conversation As Found in Tuo Nifaro Movie by Brams Zega. The objectives of this study are to find out kinds of illocutionary act performed by Gala as the main character in Tuo Nifaro movie. The Descriptive qualitative was used in the analysis of theIllocutionary Acts. The data of this thesis is derived from identify and classify the types of Illocutionary acts in Tuo Nifaro movie’s transcription that performed by Gala. The data showed that there were 59 Illocutionary Acts that appeared in Gala’s utterances. The data analysis indicated that Gala as the main character in Tuo Nifaro movie applied five Illocutionary Acts based on Searle: Assertives, Directives, Commissives, Expressives, and Declaratives. The dominant type of Illocutionary Acts is Directives, because the amount reaches is 34 i.e 57.62%. Meanwhile Assertives is 8 i.e 13.55%, Commissives is 3 i.e 5.10%, Expressives is 9 with 15.25%and Declaratives is 5 i.e 8,47%. The writer would like to give suggestions to the movie’s script writer who should be add knowledge about Illocutionary acts in the making of movie script to get a language that captivates the audience and to the other researchers who interested in conducting the research about pragmatics especially in illocutionary acts, this research can be used as the references in conducting the research about illocutionary acts.